Co-Extraction of DNA and RNA from Candida albicans Using a Chemical Method in Conjunction with Silicon Carbide with Few Cells - Elizabeth Cristina Vieira de Freitas; Francisca Alves dos Santos; Maria Raíssa Vieira Lopes; Dárcio Luiz de Sousa Júnior; Tássia Thaís Al Yafawi; Ana Carolina Ferreira Araújo; Priscilla Ramos Freitas; Irwin Rose Alencar de Menezes; Henrique Douglas Melo Coutinho; Maria Karollyna do Nascimento Silva Leandro (DNA)
Objective: The study aimed to optimize protocols for the joint extraction of deoxyribonucleic acid (DNA) and ribonucleic acid (RNA) from 0.025 × 106 CFU of Candida albicans, targeting to overcome the challenges in the extraction of these genetic materials. Materials and methods: From this, treated silicon carbide (SiC) granules were added to fungal samples from methods 1, 2, and 3 obtained from aliquots of BHI or Sabouraud medium to cause cell lysis and enable the isolation of these macromolecules by phenol and chloroform. The concentration and integrity of the extracted nucleic acids were analyzed, respectively, by spectrophotometry using the A260/A280 ratios and 1% agarose gel electrophoresis. Results: Therefore, method 3 is the one that most comprises samples considered pure of both DNA and RNA, simultaneously. Furthermore, the presence of intact RNAs corresponding to the base pair size such as 5.8 S rRNA and tRNA was verified during electrophoresis, considering the particularities of RNA, which makes it very unstable and easily degraded. Conclusions: Thus, it results in a faster and simpler method in addition to obtain promising results using minimal amounts of biological sample and offering a valuable alternative for small laboratories to work with molecular biology.